Effect of monobasic/dibasic phosphate salts on the crystallinity, physical properties and photocatalytic performance of Ag3PO4 material - Hung Nguyen Manh; Oanh Le Thi Mai; Chung Pham Do; Mai Vu Thanh; Anh Nguyen Thi Diep; Dao La Bich; Hang Lam Thi; Duyen Pham Thi; Minh Nguyen Van (AIMS Materials Science, 2022)
Ag3PO4 was prepared by the precipitation method using monobasic/dibasic phosphate salts (K2HPO4, KH2PO4, Na2HPO4, NaH2PO4) as a precipitating agent. The environment created by the precursor salts strong affected on the crystallinity and the morphology of Ag3PO4. Ag3PO4 synthesized from dibasic phosphate salts exhibited pseudospherical morphology and small particle size while monobasic phosphate salts promoted crystallization, resulting in a large grain size and a very diverse grain morphology. Ag3PO4 prepared from dibasic phosphate salts (K2HPO4 and Na2HPO4) exhibited superior photocatalytic ability, completely degrading rhodamine B (RhB) in 8 min and 10 min under Xenon lamp irradiation, respectively. This result once again confirms the necessity of particle size reduction in the production of photocatalysts.